Relationship Between Medication Adherence and Blood Sugar Levels Among Diabetes Mellitus Outpatients - Ida Untari; Sri Utami; Muhammad Hafiduddin; Asmirati Yakob; Yuli Kusumawati; Lina Alfiyani; Umi Budi Rahayu; Sri Sat Titi Hamranani; Devid Noor Umam (Faculty of Public Health, Hasanuddin University, Makassar, 2024)
Diabetes Mellitus (DM) is a disease with progressively increasing prevalence every year and often leads to complications when not properly managed. Control or success of treatment is influenced by adherence of patients to the treatment process. This study aimed to analyze relationship between medication adherence and fasting glucose levels among DM outpatients. A correlation study was conducted using a cross-sectional approach on a sample of 300 respondents selected by probability sampling technique from the entire population. The instrument used was the MMAS-8 Test (Morisky Scale Medication Adherence Scales-8) and examination of fasting sugar levels. Meanwhile, data analysis was conducted with the Spearman Rho test. The results showed that the highest treatment adherence was in the moderate category by 130 (43.3%) and a decrease in fasting sugar levels was observed among 230 (76.7%) respondents. A significant relationship was found between medication adherence and fasting glucose levels with a p-value = <0.001 and r: -0.597. Based on the results, there was a negative relationship between medication adherence and fasting blood sugar. The higher medication adherence, the better the fasting sugar levels in DM outpatients.